An examination of student outcomes in studio chemistry. Issue 1 (12th December 2016) - Kiste, Alan L.; Scott, Gregory E.; Bukenberger, Jesse; Markmann, Miles; Moore, Jennifer
Abstract : Twenty years ago, a major curriculum revision at a large, comprehensive university in the Western United States led to the implementation of an integrated lecture/laboratory (studio) experience for our engineering students taking general chemistry. Based on these twenty years of experience, construction of four purpose-built studio classrooms to house the majority of the remaining general chemistry courses was completed in 2013. A detailed study of the effects of the entire ecology of the studio experience on student success was initiated at that time. Data from content knowledge pre- and post-tests, learning attitudes surveys, and student course evaluations show positive effects on student performance, the development of more expert-like learning attitudes, increased student engagement, and increased student–instructor interactions vs. the previous separate lecture and laboratory instruction for non-engineering students. Our data also show that an associated new peer Learning Assistant program increases student engagement while also having positive impacts on the Learning Assistants themselves.